Long-term stability in the winter diet of the Japanese serow (Artiodactyla, Caprinae) - Hiruma, Mitsuko; Tochigi, Kahoko; Kishimoto, Ryosuke; Kuroe, Misako; Trentin, Bruna Elisa [UNESP]; Koike, Shinsuke (Pensoft Publishers, 2022)
The winter diets of northern ungulates are sensitive to changes in environmental conditions and ungulate population densities. We hypothesized that the winter diets of smaller browser ungulates might not readily change in response to fluctuating environmental conditions. We analyzed long-term trends in the winter diet of the Japanese serow (Capricornis crispus) by analyzing rumen contents of 532 individuals over a span of 16 years among five populations along with changes in the population densities of sika deer (Cervus nippon) in Nagano Prefecture, central Japan. The winter diet composition of the serow was stable over the long term despite the increase in deer population density. The little-flexible nature of the serow diet may explain the long-term stability in the winter diets.
Keywords: browser; Capricornis crispus; Cervus nippon; population dynamics; sika deer; ungulate